Kajian Sosiolinguistik Penggunaan Bahasa Alih Kode Terhadap Film Imperfect The Series Episode 10 Dan 11 Karya Ernest Prakasa - Nabilah Umi Rahmawati (LPPM Politeknik Pratama, 2023)
The results of this study will be described: The use of sociolinguistics to study code transformation, mixed cipher and the value of character education in the film Imperfect. The direct researcher serves as the main research tool and the film serves as a secondary tool. The method used in this study is descriptive qualitative using sociolinguistic methods. The source of the data in this study is the observational documentation of the film series using a film entitled Imperfect The Series. The data is in the form of dialogue between characters in the film and data collection using viewing and note-taking technology. The data method used is interactive analysis through data collection, data reduction, data viewing and data review. The results of the study show that